2019
DOI: 10.2147/jpr.s187798
|View full text |Cite
|
Sign up to set email alerts
|

<p>Neuroleptanalgesia for acute abdominal pain: a systematic review</p>

Abstract: Background Acute abdominal pain (AAP) comprises up to 10% of all emergency department (ED) visits. Current pain management practice is moving toward multi-modal analgesia regimens that decrease opioid use. Objective This project sought to determine whether, in patients with AAP (population), does administration of butyrophenone antipsychotics (intervention) compared to placebo, usual care, or opiates alone (comparisons) improve analgesia or decrease opiate consumption (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Additionally, haloperidol binds to the histamine receptors, alpha-2 adrenergic receptors, 5HT-2 receptors and NMDA receptors and decreases hyperalgesia produced by chronic opioid use. 47 Droperidol is a butyrophenone derivative with potent dopamine D2 antagonist actions with additional actions such as A2 adrenoceptor agonist and 5HT-3, muscarinic and nicotinic receptors antagonist. 48 Haloperidol and droperidol have been used in the ED as an adjunct in treatment of headache, 49 abdominal pain associated with cannabinoid hyperemesis syndrome, 50 gastroparesis and cyclic vomiting syndrome, 51 and chronic pain not responsive to opioids.…”
Section: Neuroleptics (Antidopaminergic Medications)mentioning
confidence: 99%
“…Additionally, haloperidol binds to the histamine receptors, alpha-2 adrenergic receptors, 5HT-2 receptors and NMDA receptors and decreases hyperalgesia produced by chronic opioid use. 47 Droperidol is a butyrophenone derivative with potent dopamine D2 antagonist actions with additional actions such as A2 adrenoceptor agonist and 5HT-3, muscarinic and nicotinic receptors antagonist. 48 Haloperidol and droperidol have been used in the ED as an adjunct in treatment of headache, 49 abdominal pain associated with cannabinoid hyperemesis syndrome, 50 gastroparesis and cyclic vomiting syndrome, 51 and chronic pain not responsive to opioids.…”
Section: Neuroleptics (Antidopaminergic Medications)mentioning
confidence: 99%
“…Haloperidol, a butyrophenone antipsychotic medication, has limited evidence for its efficacy in acute pain, and studies have focused on the use of oral antipsychotics as adjunctive therapies [4]. In fact, in a recent systematic review of butyrophenone antipsychotics for acute abdominal pain, the authors concluded "we cannot draw a conclusion on the efficacy or benefit of neuroleptanalgesia in the management of patients with [acute abdominal pain]" [5]. However, recent educational programs have also emphasized the role of haloperidol for chronic pain patients in the ED with little supporting evidence [6].…”
Section: Introductionmentioning
confidence: 99%